2016
DOI: 10.1364/oe.24.024600
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared nonlinear absorption in As_2S_3 chalcogenide glass

Abstract: We report mid-infrared (MIR) nonlinear absorption in As2S3 glasses which results from two-photon excitation of valence electron to the Urbach extension followed by strong linear absorption of excited states. The measured MIR nonlinear absorption can be 3 to 4 orders of magnitude stronger than the two-photon absorption in the near-infrared for similar laser intensities and does not result from contaminants, but it is intrinsic to As2S3 glasses. As2S3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…4(b) illustrate the presence of a valley in the center of each trace, which can be attributed to reverse-saturated absorption. Given that the normalized photon energy (hv/E g , where hv = 1.55 eV is the incident photon energy at 800 nm) of the samples between 0.6 and 0.7 were within the two-photon absorption region (TPA; 0.5 < hv/E g < 1) [30], we can ascribe the nonlinear absorption behavior of the GIC parent glass and ChGCs at 800 nm to the TPA process. The corresponding M A N U S C R I P T…”
Section: -1385) Crystallites According To the Reference Given At Thmentioning
confidence: 99%
“…4(b) illustrate the presence of a valley in the center of each trace, which can be attributed to reverse-saturated absorption. Given that the normalized photon energy (hv/E g , where hv = 1.55 eV is the incident photon energy at 800 nm) of the samples between 0.6 and 0.7 were within the two-photon absorption region (TPA; 0.5 < hv/E g < 1) [30], we can ascribe the nonlinear absorption behavior of the GIC parent glass and ChGCs at 800 nm to the TPA process. The corresponding M A N U S C R I P T…”
Section: -1385) Crystallites According To the Reference Given At Thmentioning
confidence: 99%
“…These unique properties, coupled with the flexible size and modifiable composition, make ChG an ideal material for infrared optics and nonlinear photonic devices. [4,5] Therefore, great efforts [2,[6][7][8][9] have been made to design ChGs that match the specifications of each particular TONL-based optical device. To evaluate the performances of ChGs for nonlinear photonic applications such as all-optical switching, wavelength conversion for an optical communication system, a key prerequisite is to design bulk glass composition regarding the figure of merit (FOM) [6,10] that considers the trade-off among nonlinear refractive, nonlinear absorption, and incident wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is improved at mid-IR wavelengths as even two photons have insufficient energy to bridge the gap, suggesting greater opportunities for power scalability. A recent study, however, identified the possibility of strong nonlinear absorption in As 2 S 3 from two-photon absorption of valence electrons to the mid-gap Urbach extension, followed by linear absorption of excited states [25]. This is not likely to be a limiting factor for the short lengths required for nonlinear compression, although further work is needed to confirm this and to explore this loss mechanism.…”
mentioning
confidence: 98%